miRNAs Contained in Extracellular Vesicles Cargo Contribute to the Progression of Idiopathic Pulmonary Fibrosis: An In Vitro Aproach - Jovito Cesar Santos-Álvarez; Juan Manuel Velázquez-Enríquez; Rosendo García-Carrillo; César Rodríguez-Beas; Alma Aurora Ramírez-Hernández; Edilburga Reyes-Jiménez; Karina González-García; Armando López-Martínez; Laura Pérez-Campos Mayoral; Sergio Roberto Aguilar-Ruiz; María de los Ángeles Romero-Tlalolini; Honorio Torres-Aguilar; et al. (Cells, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive lung disease. Lesions in the lung epithelium cause alterations in the microenvironment that promote fibroblast accumulation. Extracellular vesicles (EVs) transport proteins, lipids, and nucleic acids, such as microRNAs (miRNAs). The aim of this study was to characterize the differentially expressed miRNAs in the cargo of EVs obtained from the LL97 and LL29 fibroblast cell lines isolated from IPF lungs versus those derived from the CCD19 fibroblast cell line isolated from a healthy donors. We characterized EVs by ultracentrifugation, Western blotting, and dynamic light scattering. We identified miRNAs by small RNA-seq, a total of 1144 miRNAs, of which 1027 were known miRNAs; interestingly, 117 miRNAs were novel. Differential expression analysis showed that 77 miRNAs were upregulated and 68 were downregulated. In addition, pathway enrichment analyses from the Gene Ontology and Kyoto Encyclopedia of Genomes identified several miRNA target genes in the categories, cell proliferation, regulation of apoptosis, pathways in cancer, and proteoglycans in cancer. Our data reveal that miRNAs contained in EVs cargo could be helpful as biomarkers for fibrogenesis, diagnosis, and therapeutic intervention of IPF.